2007
DOI: 10.1007/s11661-006-9063-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of Laser-Beam-Welded Directionally Solidified INCONEL 738

Abstract: The laser welding of a directionally solidified INCONEL 738 superalloy (DS IN738) was investigated. Microstructural analysis of the fusion zone (FZ) and the heat-affected zone (HAZ) revealed that cracking occurred mainly in HAZ with only some cracks being extended into the FZ. However, the frequently observed centerline cracking in FZ of DS and single crystal (SX) alloys did not occur, which was attributed to the presence of negligible volume fraction of c-c¢ eutectic in FZ. Constitutional liquation of seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…To date, many efforts have been made to eliminate or reduce the HAZ cracking of precipitation-hardened Ni-base superalloys through the control of primary microstructures by preweld heat treatment [18,19,[22][23][24], by laser [12,18,20,23,[25][26][27] or electron beam [28,29] welding processes, or by using filler with lower Al + Ti content [30][31][32]. In practical applications, the use of under matched filler or low heat-input welding processes to reduce weld-shrinkage stress are able to lower cracking in those Ni-base superalloys with poor weldability.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many efforts have been made to eliminate or reduce the HAZ cracking of precipitation-hardened Ni-base superalloys through the control of primary microstructures by preweld heat treatment [18,19,[22][23][24], by laser [12,18,20,23,[25][26][27] or electron beam [28,29] welding processes, or by using filler with lower Al + Ti content [30][31][32]. In practical applications, the use of under matched filler or low heat-input welding processes to reduce weld-shrinkage stress are able to lower cracking in those Ni-base superalloys with poor weldability.…”
Section: Introductionmentioning
confidence: 99%
“…MC carbides, M5B3 and M3B2 borides, and Ni7Hf2 intermetallics associated with γ′ precipitates in the γ matrix were identified. In the prior studies [8,19], complex grain boundary constituents, such as MC carbides, M2SC sulphocarbides, Cr-Mo borides, Ni-Zr intermetallic compound and γ-γ′ (Ni3(Al,Ti)) eutectics were obtained in IN738/IN738LC superalloy. The presence of those terminal solidification products at interdendritic boundaries was inevitably detrimental to the weldability of the cast Mar-M004 superalloy.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Liquidation cracking in the HAZ is one of the most noticeable problems in welding or repair-welding of Ni-based superalloys such as IN 738 [7][8][9], Rene 80 [10][11][12][13], IN 939 [14,15], RR 1000 [16], IN 713C [17], and K465 [18]. Grain boundary liquation results from incipient melting of MC carbides, Cr-Mo borides, γ-γ eutectic and Ni-Zr intermetallics along the solidified boundaries [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively studied and reported that primary γ' precipitates constitutionally liquated within the heat affected zone of different nickel-based superalloys during different welding techniques [12,13,19,20], thus, that is not the focus of this paper. In this work, aside from the primary γ' precipitates that were observed to liquate constitutionally within the weld heat affected zone, the M 3 B 2 precipitates found in the parent alloy have also been observed to liquate within the heat affected zone (150-360 μm from the weld bond line).…”
Section: Microstructure Of the Welded Alloymentioning
confidence: 99%